Development of a performance evaluation method of mechanical sand retention techniques - Samsuri, Ariffin; Tan, C. H. (2001)
The production of sand from poorly consolidated formation is a problem that has plagued the oil and gas industry for a long time. The problem of sanding can be alleviated by producing under the critical flow rate that triggers sand production. However, this critical production rate is usually small and uneconomical. Therefore, some from of sand control is employed of which the mechanical sand retention, i.e. gravel pack and sand control screen are the most popular. The use of sand control devices inevitably causes decline in well productivity, which is characterized by the additional pressure drop across the device(s). The drop in productivity is often aggravated by high velocity and two-phase flow. A computer simulation program will be developed to evaluate the prodcutivity of gravel pack and sand control screen with a few assumptions such as semi-steady state flow around the wellbore, perforations are treated as perfect cylinders and the annulus between the perforation and screen is completely filled with gravel. For screen only completion, the natural sand bridging will not be considered. For the gravel pack, a three-dimensional, two-phase finite difference scheme will be developed that is capable of modelling the dispersed flow pattern, which exists in the gravel pack. The effect of turbulence would be accounted for by means of the Forschheimer's equation. A dedicated, CFD based model will be used to study the fluid flow across sand control screens. The pressure drop associated with perforations will be calculated using correlations based on the finite-element modeling. Such phenomena as partial penetration, drilling damage and perforation damage will be included. The resulting package can be used to study the effect on overall productivity of such factors as perforation density, geometry, flow rate and fluid properties.